On the definition of height reference surfaces over an arbitrary selected area by means of DFHRS approach. Issue 4 (1st October 2016) - Ameti, Perparim; Jäger, Reiner
Abstract: The aim of this study is to analyze the best fitting geoid model for an arbitrary selected area of investigation. The Digital Finite Element Height Reference Surface (DFHRS) method, developed by Hochschule Karlsruhe has been chosen to define the height reference surface for the territory of Kosovo, which should be defined as national vertical datum. This approach allows the conversion of ellipsoidal heights determined by GPS into the standard heights, which refer to the height reference surface (HRS) of an orthometric, or normal surface system. The DFHRS is defined as continues HRS in arbitrary large areas by bivariate polynomials over an irregular grid (Jäger, Schneid 2001). The DFHRS approach uses wide range of the input data (Geometric and Physical) and in our case there were 30 GPS/leveling height data as well as physical derivatives from different global geopotential models. The proposed approach has been successfully applied and results are compared to actual normal heights and in selected profiles of digital elevation reference surface calculated from the national control network. Special attention has been given to the choice of the geopotential model and the selection of the pass points in source and target surface.